Transnational corporations as a challenge for contemporary international space law - Ziemblicki, Bartosz (Право и государство, 2018)
This article considers the legal aspects of space activities of transnational corporations. In today’s world private entities took over space conquest initiative started by the states. However, the international space law regime is over half- century-old and does not respond to contemporary challenges. This article includes a detailed analysis of three particular problems: ownership, liability and status of flight participants. The author concludes that there are more and more questions that the existing regulations fail to answer.
Keywords: transnational corporations; space law; astronauts; asteroid mining; outer space; treaty; international liability; Research Subject Categories::LAW/JURISPRUDENCE